Pertahanan Keluarga Sakinah Mawaddah Warrohmah Pada Era Digitalisasi dan Kontribusinya Terhadap Pembaruan Hukum Nasional - Fu’ad, Asep; Mukhlas, Oyo Sunaryo; Saebani, Beni Ahmad; Husain, Husain (Dialog Legal: Jurnal Syariah, Jurisprudensi dan Tata Negara, 2026)
This research is motivated by the rapid advancement of digitalization, which has significantly impacted the resilience of Muslim families in Indonesia. Issues such as online infidelity, gadget addiction, and declining communication quality within households pose serious challenges to the values of sakinah, mawaddah, and rahmah as taught in Islam. Based on these problems, this study seeks to examine the ideal concept of sakinah, mawaddah, rahmah from the perspective of Islamic law, analyze the implications of digitalization on Muslim family resilience, and formulate strategies to safeguard family values in accordance with Islamic principles. The research employs a qualitative library-based approach, analyzing classical Islamic literature, legal regulations, national legislation, and contemporary social phenomena. The findings reveal that the concept of sakinah, mawaddah, rahmah requires contextual actualization in the digital era, while digitalization indeed poses serious implications for family stability. Effective strategies include strengthening communication, enhancing digital literacy, reinforcing religiosity, and adopting selective adaptation toward technology. Furthermore, the study contributes to the renewal of family law in Indonesia, ensuring its responsiveness to modern challenges.